The Effect of Tax Planning, Earning Volatility, and Financial Statement Integrity on Firm Value with Financial Stability as a Moderator in Southeast Asia - Anis Masluhah; Tambun, Sihar (JURNAL MANAJEMEN MOTIVASI, 2026)
This study tests the effects of tax planning, earnings volatility, and financial statement integrity on firm value, with financial stability as a moderator, among Southeast Asian technology firms (2022–2024). From the Indonesia, Malaysia, and Singapore stock exchanges, 29 firms were selected (87 firm-year observations). Random-effects panel regression with interaction terms indicates no direct impact of tax planning, earnings volatility, or reporting integrity on firm value, and no moderating effect of stability on tax planning or integrity. Yet stability significantly amplifies a negative volatility–value relationship: when firms are financially stable, higher earnings volatility lowers market valuation. Keywords: Earning Volatility; Financial Stability; Financial Statement Integrity; Firm Value; Tax Planning